2017
DOI: 10.1016/j.ijom.2017.02.483
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of dickkopf WNT signaling pathway inhibitor 3 in the malignant progression of oral submucous fibrosis

Abstract: Objectives: Increase of regulatory T cells (Tregs) in the tumour microenvironment predicts worse survival of patients with various types of cancer including tongue squamous cell carcinoma (TSCC). Recently, the cross-talk between Tregs and regulatory B cells (Bregs) has been shown in several tumour models. However the relevance of Bregs to tumour immunity in humans remains elusive. Our objective was to investigate the distribution and function of Bregs in TSCC microenvironment. Methods: Double staining (Bregs: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…DKK1 expression was different from the expression of DKK3 . DKK3 is upregulated in the carcinogenesis of OSF 24 . Statistical analysis indicated that the downregulation of DKK1 may affect OSF pathogenesis and malignant transformation.…”
Section: Discussionmentioning
confidence: 96%
“…DKK1 expression was different from the expression of DKK3 . DKK3 is upregulated in the carcinogenesis of OSF 24 . Statistical analysis indicated that the downregulation of DKK1 may affect OSF pathogenesis and malignant transformation.…”
Section: Discussionmentioning
confidence: 96%